2020
DOI: 10.1002/emp2.12214
|View full text |Cite
|
Sign up to set email alerts
|

360 virtual reality pediatric mass casualty incident: A cross sectional observational study of triage and out‐of‐hospital intervention accuracy at a national conference

Abstract: Objective With adolescent mass casualty incidents (MCI) on the rise, out‐of‐hospital readiness is critical to optimize disaster response. We sought to test the feasibility and acceptability of a 360 Virtual Reality (360 VR) platform for disaster event decisionmaking. Methods This was a cross‐sectional observational assessment of a subject's ability to triage and perform out‐of‐hospital interventions using a 360 VR MCI module. A convenience sample of attendees was recrui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 29 publications
0
32
0
Order By: Relevance
“…The second focus of VS-integrated learning contexts in undergraduate medical education was emergency and pediatric emergency medicine training, with 14 articles ( 10 , 16 – 18 , 29 , 30 , 34 , 39 , 51 , 55 , 68 , 79 , 93 , 101 ) published recently. Among them, eight studies ( 10 , 16 – 18 , 30 , 34 , 39 , 68 ) used VS-based teaching in pediatric emergencies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second focus of VS-integrated learning contexts in undergraduate medical education was emergency and pediatric emergency medicine training, with 14 articles ( 10 , 16 – 18 , 29 , 30 , 34 , 39 , 51 , 55 , 68 , 79 , 93 , 101 ) published recently. Among them, eight studies ( 10 , 16 – 18 , 30 , 34 , 39 , 68 ) used VS-based teaching in pediatric emergencies.…”
Section: Resultsmentioning
confidence: 99%
“…The above studies showed the integration of VS in emergency medicine training provided promising zero-risk training for undergraduates. In particular, seven studies ( 18 , 29 , 30 , 34 , 39 , 93 , 101 ) used the VR simulation systems consisting of VR headsets or goggles to realistically and immersively replicate clinical settings and findings, allowing students to deliberately practice and receive vivid feedback on their assessment.…”
Section: Resultsmentioning
confidence: 99%
“…Beyond the need for academic communication and expositions, virtual conferences also serve as suitable training and skills development environments. As Lowe et al discuss, virtual environments have the potential to be widely adopted for disaster readiness training and education [39]. In their investigation, they document the feasibility of 360 VR technology for adolescent disaster readiness.…”
Section: Methodsmentioning
confidence: 99%
“…Participants could even earn approved Continuing Medical Education (CME) credits by completing uRCADE games, highlighting their effectiveness and utility. [18]. Actors created realistic scenes of a care point involving 150 potential pediatric casualties, with the immersive virtual reality story allowing users to select triage categories and decide on interventions.…”
Section: Gamification In General Medical Educationmentioning
confidence: 99%